Religijny wymiar aktywności społecznej w protestanckim środowisku łódzkich przemysłowców w XIX-XX w. Na przykładzie rodzin Scheiblerów, Herbstów i Geyerów - Woźniak, Krzysztof Paweł (Studia Europaea Gnesnensia, 2018)
The article outlines the outcomes of social activities undertaken by the elites of Protestant industrialists of Łódź in the 19th and 20th century, highlighting the religious motivations behind their initiatives. The author draws attention to the correlation between the Protestant worldview and ethics and the demands of the nascent capitalism, in the circumstances where the state failed to address the numerous social problems of the times.